Does addition of metoclopramide to lignocaine confer additional advantage on reducing pain on propofol injection? - Girija Kumari B; Samantaray A; Geeta K; Durga P; Ramchandran G; Kiran Kumar A; Jagadeesh G (Journal of Clinical and Scientific Research, 2015)
Background: Intravenous injection of lipid emulsion propofol induces a considerable degree of pain and the most preferred treatment suggested is pretreatment with intravenous lignocaine to alleviate such pain. The present study was designed to evaluate whether addition of metoclopramide to lignocaine offers any advantage over lignocaine alone as a pretreatment in prevention of pain following propofol injection. Methods: In this prospective, randomized, double-blind controlled study, 60 patients were randomized to receive either lignocaine (group A) or lignocaine with metoclopramide (group B) intravenously as a pretreatment before injection of propofol. Pain due to injection of propofol was assessed with a four point categorical verbal rating pain scale. The incidence and magnitude of pain was compared between the two groups. Results: There was no statistically significant difference in the perceived intensity of pain between the two groups at different time points after administration of propofol. The incidence of moderate pain was 23.3% in group A and 20% in group B (p = 0.211); 26.7% patients in group A and 43.3% patients in group B had no pain during propofol administration (p = 0.116). Conclusions: Addition of metoclopramide to lignocaine does not have additional advantage over lignocaine alone in alleviating the pain of emulsified propofol injection.